Algorithms for Selecting a Set of Geological Exploration Methods to Solve Problems of Oil and Gas Prospecting and Exploration Using the Example of the Pur-Taz Oil and Gas Region - A. A. Polyakov; A. V. Stoupakova; N. A. Malyshev; R. S. Sautkin; O. V. Trutneva; V. E. Verzhbitsky; D. K. Komissarov; S. V. Osipov; A. P. Antonov; V. G. Lakeev; R. V. Lukashev (Georesursy, 2025)
Modern geological exploration is a complex process that involves a series of research stages, each aimed at solving specific tasks in order to identify oil and gas reserves. These stages are typically carried out in a sequential manner, with the results being integrated as they are obtained. This process typically starts with a general analysis of the region where the search object is located, and then moves on to more detailed studies of the local area in order to gain a better understanding of the structure of the deposit. In this paper, we have developed algorithms for an integrated approach to exploration, which depend on the level of knowledge about the object being studied. We have also conducted an analysis of retrospective methods at different stages of exploration, using one of the most well-studied areas in the Pur-Taz oil and gas region as an example. The most poorly understood aspects of the field development stage include determining the timing of the arrival of hydrocarbons in the trap and the timing of structural changes in the hydrocarbon system. The lack of research into these regional factors leads to the loss of potential deposits. Using an example from one of the fields, we illustrate how we solved problems that had not been addressed before, such as restoring the paleostructure on a regional and zonal scale. This resulted in the identification of new promising areas for oil and gas exploration within the Pur-Taz area.